Environmental scanning practice of enterprise 50 Small Medium Enterprise (E50 SMEs) in Malaysia - Othman, Roslina; Hamedon, Siti Rohimi (2011)

(untitled)
This study investigates the effects of organizational and owner/ manager profile on environmental scanning practice of Enterprise 50 Small Medium Enterprise (E50 SMEs) in Malaysia. It investigates the extent of environmental scanning practice and the factors related to information sources that E50 SMEs utilized for environmental scanning. Based on the constructs of the measures, a research scale was developed for the study and data were collected via self-administered mail survey among the E50 SMEs in Malaysia. The results showed positive effects of organizational and owner/ manager profile on environmental scanning practice of E50 SMEs. There are also findings on the extent environmental scanning on the business environment sectors of E50 SMEs with respect to utilization of information sources. Implications of our findings for SMEs owner/ managers and practitioners, the study’s limitations and future research directions are subsequently addressed.